Elegy in blue - Helprin, Mark (Abrams Press, 2026)
High in a subsidized studio apartment, the unnamed eighty-two-year-old narrator of Elegy in Blue looks out across the rooftops of Brooklyn all the way to the sea. His distinguished career on Wall Street is in ruins, his mansion in Brooklyn Heights has been burned to the ground, and most of all, his father, his son, and his wife - the stunningly beautiful and equally kind Clare - have been taken from him, one by one, over the decades, by war and an act of antisemitic violence. Now his "allegiance is to this ghosts." He's almost lost to memory, reflection, and a purposeful letting go of life. But when violence threatens to destroy another family, he takes drastic action in hope of restoring a portion of justice to the world. Can he fashion his life into an elegy, one that heals a broken heart and relieves the sting of death?